The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1097/ftd.0b013e31828c1581
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms in ABCB1 Influence the Pharmacodynamics of Tacrolimus

Abstract: The ABCB1 3435C>T SNP influences ABCB1 activity of T cells and the pharmacodynamic effect of tacrolimus in kidney transplant patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 37 publications
1
18
2
1
Order By: Relevance
“…future science group primarily tacrolimus and cyclosporine pharmacokinetics [63,64]. Larger, well-powered studies are needed to validate our findings.…”
Section: Limitationssupporting
confidence: 54%
“…future science group primarily tacrolimus and cyclosporine pharmacokinetics [63,64]. Larger, well-powered studies are needed to validate our findings.…”
Section: Limitationssupporting
confidence: 54%
“…For example, Yoon and colleagues have showed that in monocytes from kidney transplant recipients homozygous for CYP3A5*3 , the HLA/DR+ mean fluorescent intensity was significantly lower compared to those from CYP3A5*1 carriers, with significant negative correlations with dose-adjusted trough blood concentrations, suggesting the HLA/DR expression on monocytes might be explored as a tool for monitoring of tacrolimus toxicity (56). In another study, Vafadari et al a showed the pharmacodynamic effect of tacrolimus on inhibiting IL-2 production depended on ABCB1 3435C>T genotype (57). …”
Section: Calcineurin Inhibitors and Pharmacodynamic Phenotypesmentioning
confidence: 99%
“…In kidney-transplanted patients, C3435T polymorphism has an impact on the efficacy of the immune suppressant tacrolimus due to a decrease of intestinal drug absorption 19 but also immunosuppression resistance of CD4 + and CD8 + T cells, observed on patients with TT genotype. 20 Other associations with specific pathologies have been established and are reviewed further in this review (cf. Part III - auto immunity and HIV).…”
Section: Introductionmentioning
confidence: 99%